Association between Stress and Tension-Type Headaches in Medical Students of the School of Medicine & Health Science, Atma Jaya University - Callista Anastasya; Julia Rahadian Tanjung; Mariani Santosa (Journal of Urban Health Research, 2023)
Introduction: Stress is the body's response to threatening external stimuli. Many medical students experience stress. Stress that medical students share can be caused by learning demands, interpersonal problems, and other things. Even though stress is daily, excessive stress can also cause various health problems, including headaches. Headache is the most common neurological problem in the world. There are several types of headaches, one of which is tension headaches. However, the relationship between stress and headaches, especially tension-type headaches in medical students, has yet to be widely studied. Methods: This study is a cross-sectional analytic observational study, on 120 pre-clinical students (22 males, 98 females) aged 18-21 from the School of Medicine and Health Sciences, Atma Jaya Catholic University in Jakarta. The questionnaire used to measure the respondent's stress levels were the Depression Anxiety Stress Scale 42 (DASS-42) and Headache Screening Questionnaire (HSQ) to determine the respondent's headache. The data obtained were analyzed statistically using the Chi-square method, with a p-value <0.05. Results: Out of 120 students, 74.2% experienced stress within normal limits, while 9.2%, 10%, 5%, and 1.7% reported experiencing mild, moderate, severe, and very severe stress levels, respectively. 30.8% of students experienced tension-type headaches, and 69.2% of students did not. The result obtained from the chi-square bivariate test was p = 0.188. Conclusions: There is no association between stress and tension-type headaches in medical students of the School of Medicine & Health Science, Atma Jaya University.   Keywords: stress, tension-type headache, DASS-42, HSQ